Ephemeral architecture : in between permanence and impermanence towards sustainable architecture / Sayed Muhammad Aiman Sayed Abul Khair and Prof Madya Dr. Ismail Samsuddin - Sayed Muhammad Aiman, Sayed Abul Khair; Ismail, Samsuddin (2015)
The arrival of the agriculture period has led to the evolution of architecture from the nomadic and shifting mode into permanence. Ephemeral is a state of lasting a very short time. It is also considered as portable architecture which existed before the agriculture period when the humans lived as hunters and gatherers. As time goes by, permanence has become a new mode and the fundamentals of architecture tomost people that understand architecture. This paper is conducted to present an understanding of definition, interpretation and application of ephemeral in architecture in between permanence and impermanence. The paper has reviewed and analyzed the definition, interpretation and characteristic of ephemeral in architecture according tothe historical and modern perspective. Besides that, an investigation has been done to determine the role that permanence plays in defining architecture and the role of ephemerality might plays within the realm of architecture. Literature review and case study are the primary and secondary data of this paper. As a result, ephemeral architecture has a significant role in built environment and sustainable architecture. By the time technology such as industrial building system and rapid prototype with 3-dimension printing construction progress, architecture has experienced sustainable growth, become flexible and resilient with demand and context. The term will not seize the general idea of architecture as an object of permanence since the static, stable and the permanent are all critical. The mobility, portability, transformability, the inflatable and the ephemeral are the essentials of stability and permanence.